Child Abuse, Neglect, and Violent Criminal Behavior in a Midwest Metropolitan Area of the United States, 1967-1988 - Widom, Cathy Spatz ([Verlag nicht ermittelbar], 1991)
These data examine the relationships between childhood abuse and/or neglect and later criminal and violent criminal behavior. In particular, the data focus on whether being a victim of violence and/or neglect in early childhood leads to being a criminal offender in adolescence or early adulthood and whether a relationship exists between childhood abuse or neglect and arrests as a juvenile, arrests as an adult, and arrests for violent offenses. For this data collection, adult and juvenile criminal histories of sampled cases with backgrounds of abuse or neglect were compared to those of a matched control group with no official record of abuse or neglect. Variables contained in Part 1 include demographic information (age, race, sex, and date of birth). In Part 2, information is presented on the abuse/neglect incident (type of abuse or neglect, duration of the incident, whether the child was removed from the home and, if so, for how long, results of the placement, and whether the individual was still alive). Part 3 contains family information (with whom the child was living at the time of the incident, family disruptions, and who reported the abuse or neglect) and data on the perpetrator of the incident (relation to the victim, age, race, sex, and whether living in the home of the victim). Part 4 contains information on the charges filed within adult arrest incidents (occasion for arrest, multiple counts of the same type of charge, year and location of arrest, and type of offense or charge), and Part 5 includes information on the charges filed within juvenile arrest incidents (year of juvenile charge, number of arrests, and type of offense or charge). The unit of analysis for Parts 1 through 3 is the individual at age 11 or younger, for Part 4 the charge within the adult arrest incident, and for Part 5 the charge within the juvenile arrest incident.